Internship in K.U.Yarn Pvt. Ltd. as Trader - Lath, Manan (ATLAS SkillTech University, 2024)
Launched in the year 2013, K.U.Yarn Pvt Ltd is a company who deals in Yarn and Yarn Raw material for industrial use. As it was a leading company in Cotton Yarn,Fabric,Textile Mills with the best rates then the market rates. Firstly, I had to completely understand all the aspects of the company was trying to create as this business was something I was never aware of and it was like an entirely new subject for me. After understanding the company’s structure , they were working on, I was assigned different tasks that to be executed by me during my 2 months of internship.
Project Report on Internship in K.U.Yarn Pvt. Ltd. as Trader (2022-24) Under the Guidance of Prof. David Wittenberg